Crossing the Rubicon : Caesar's decision and the fate of Rome - Fezzi, Luca (Yale University Press, 2019)
A dramatic account of the fateful year leading to the ultimate crisis of the Roman Republic and the rise of Caesar's autocracy. When the Senate ordered Julius Caesar, conqueror of Gaul, to disband his troops, he instead marched his soldiers across the Rubicon River, in violation of Roman law. The Senate turned to its proconsul, Pompey the Great, for help. But Pompey's response was unexpected: he commanded magistrates and senators to abandon Rome-a city that, until then, had always been defended. The consequences were the ultimate crisis of the Roman Republic and the rise of Caesar's autocracy. In this new history, Luca Fezzi argues that Pompey's actions sealed the Republic's fate. Drawing on a wide range of primary sources, including Cicero's extensive letters, Fezzi shows how Pompey's decision shocked the Roman people, severely weakened the city, and set in motion a chain of events that allowed Caesar to take power. Seamlessly translated by Richard Dixon, this book casts fresh light on the dramatic events of this crucial moment in ancient Roman history.